2017
DOI: 10.3892/ijo.2017.4129
|View full text |Cite
|
Sign up to set email alerts
|

Canonical and non-canonical WNT signaling in cancer stem cells and their niches: Cellular heterogeneity, omics reprogramming, targeted therapy and tumor plasticity (Review)

Abstract: Cancer stem cells (CSCs), which have the potential for self-renewal, differentiation and de-differentiation, undergo epigenetic, epithelial-mesenchymal, immunological and metabolic reprogramming to adapt to the tumor microenvironment and survive host defense or therapeutic insults. Intra-tumor heterogeneity and cancer-cell plasticity give rise to therapeutic resistance and recurrence through clonal replacement and reactivation of dormant CSCs, respectively. WNT signaling cascades cross-talk with the FGF, Notch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
362
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 369 publications
(368 citation statements)
references
References 166 publications
6
362
0
Order By: Relevance
“…A large body of evidence demonstrated that activation of Wnt signaling is involved in controlling the malignant features of CSC through increased EMT, which leads to cancer invasion and metastasis (Katoh, 2017, Webster et al, 2015, Zhan et al, 2017). Knockdown of CD133 by the virally delivered short hairpins of RNA in human metastatic melanoma FEMX-I cells impeded cell motility and their ability to form spheroids (Rappa et al, 2008).…”
Section: Cd133 and Its Signaling In Cancer Metastasismentioning
confidence: 99%
“…A large body of evidence demonstrated that activation of Wnt signaling is involved in controlling the malignant features of CSC through increased EMT, which leads to cancer invasion and metastasis (Katoh, 2017, Webster et al, 2015, Zhan et al, 2017). Knockdown of CD133 by the virally delivered short hairpins of RNA in human metastatic melanoma FEMX-I cells impeded cell motility and their ability to form spheroids (Rappa et al, 2008).…”
Section: Cd133 and Its Signaling In Cancer Metastasismentioning
confidence: 99%
“…In the canonical pathway (WNT/β-catenin/TCF), a WNT ligand forms a ternary complex with the seven-pass transmembrane receptor, Frizzled (Fzd) and low-density lipoprotein receptor-related protein 5/6 (LRP5/6), which activates Dvl homolog 1 (Dvl1) (26,27). Activation of Dvl1 dismantles the β-catenin 'destruction' complex to which it is associated, composed of Axin1 (AXIN1), adenomatous polyposis coli (APC), GSK3β and casein kinase 1 (CK1), which promotes the recruitment of β-catenin and TCF to the WNT target-gene promoters in the nucleus, to subsequently induce the transcription of target genes, including c-Myc and cyclin D1 (28).…”
Section: Growth Factor and Wnt Pathwaysmentioning
confidence: 99%
“…Therefore, targeted inhibition of Fzd represents a rational and promising novel approach for cancer therapy (39). An ongoing clinical trial is evaluating vantictumab and ipafricept (27).…”
Section: Wnt-related Potential Candidates For Overcoming Chemoresistancementioning
confidence: 99%
“…Currently, cancer stem cells have been identified in a number of cancers including breast and colon (193). Pathways implicated in cancer stem cell renewal include Wnt (194), janus kinase (Jak), bone morphogeneic protein (BMP), and octamer-binding transcription (Oct-4) signaling pathways (193). Natural dietary compounds have been shown to regulate CSCs by increasing their sensitivity to chemotherapeutic agents, enhancing their differentiation, and inhibiting their self-renewal signaling (195, 196).…”
Section: Pathways Targeted In Cancer Chemopreventionmentioning
confidence: 99%